How do Independent Directors View Carbon Information Disclosure? Evidence From China - Khan, Haroon Ur Rashid; Khidmat, Waqas Bin; Al Hares, Osama; Awan, Sadia; Saleem, Kashif (Frontiers in Environmental Science, 2022)
This study examines the effect of independent directors on carbon information disclosure (CID) in China from 2011 to 2017. Additionally, this study investigates the effect of independent director’s attributes (gender, academic experience, and political connection) on the CID. To test our hypothesis, we collected data of 511 Chinese listed firms. The empirical results show that independent directors have a positive influence on the CID. Moreover, the independent female directors, independent academic directors and independent politically connected directors also enhances the CID. Our findings offer shareholders, regulators, and other stakeholders an integrating perspective on motivating firms to disclose high quality carbon information.